1985
DOI: 10.1111/j.2042-3306.1985.tb02056.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology and therapeutic uses of non‐steroidal anti‐inflammatory drugs in the horse

Abstract: Summary Weak organic acids possessing anti‐inflammatory, analgesic and antipyretic properties — commonly known as aspirin‐like drugs — have been used in equine medicine for almost 100 years. These non‐steroidal anti‐inflammatory drugs (NSAIDs) may be classified chemically into two groups; the enolic acids such as phenylbutazone and carboxylic acids like flunixin, meclofenamate and naproxen. All NSAIDs have similar and possibly identical modes of action accounting for both their therapeutic and their toxic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
10

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 35 publications
(36 reference statements)
7
83
0
10
Order By: Relevance
“…Individual plasma levels varied too greatly with both drugs to allow correlation of plasma levels with analgesic effect; the same has been shown before for carprofen at similar plasma concentrations (Lascelles et al, 1998). Studies in horses and calves concluded that plasma drug concentrations of NSAID are not a useful guide to therapeutic activity at any given time (Higgins and Lees, 1984;Lees and Higgins, 1985).…”
Section: Discussionmentioning
confidence: 75%
“…Individual plasma levels varied too greatly with both drugs to allow correlation of plasma levels with analgesic effect; the same has been shown before for carprofen at similar plasma concentrations (Lascelles et al, 1998). Studies in horses and calves concluded that plasma drug concentrations of NSAID are not a useful guide to therapeutic activity at any given time (Higgins and Lees, 1984;Lees and Higgins, 1985).…”
Section: Discussionmentioning
confidence: 75%
“…As a follow-up to this initial study, they tested the efficacy of oral creatine as a mediator of acute and chronic inflammation in rats, as well as the ability of creatine to function as an analgesic [19]. In a model of carrageenan-induced acute inflammation of the foot paw, creatine suppressed inflammation as effectively as the control drug phenylbutazone [19], a nonsteroidal anti-inflammatory drug (NSAID) used in animals [196,197]. Because serotonin (also referred to as 5-HT) plays a significant role in the early stages of inflammation in the carrageenan model [189,192], the authors utilized the serotonin-induced model of paw edema to verify the utility of oral creatine as an anti-inflammatory agent [198] and found that creatine-fed animals had reduced inflammation compared to control-treated animals [198].…”
Section: Creatine As An Anti-inflammatory Agentmentioning
confidence: 99%
“…The precise site and mode of action are still unknown but it may act peripherally in inflamed tissue, probably by inhibiting the enzyme COX to decrease the formation of precursors of prostaglandins and possibly by inhibiting other local mediators of the inflammatory response (Lees and Higgins, 1985). In our study, flunixin meglumine was not an effective drug for the provision of analgesia in 5 dpf zebrafish, as fish spent significantly less time swimming compared with control larvae.…”
Section: Experiments 1: Impact Of Noxious Chemicals On Larval Behaviourmentioning
confidence: 41%